2012
DOI: 10.1088/0004-637x/759/1/62
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP BETWEEN LOW AND HIGH FREQUENCIES IN δ SCUTI STARS: PHOTOMETRICKEPLERAND SPECTROSCOPIC ANALYSES OF THE RAPID ROTATOR KIC 8054146

Abstract: Two years of Kepler data of KIC 8054146 (δ Sct/γ Dor hybrid) revealed 349 statistically significant frequencies between 0.54 and 191.36 cycles day −1 (6.3 μHz to 2.21 mHz). The 117 low frequencies cluster in specific frequency bands, but do not show the equidistant period spacings predicted for gravity modes of successive radial order, n, and reported for at least one other hybrid pulsator. The four dominant low frequencies in the 2.8-3.0 cycles day −1 (32-35 μHz) range show strong amplitude variability with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 22 publications
(26 reference statements)
2
44
0
Order By: Relevance
“…Wu 2001 andMontgomery 2005). Combination frequencies dominate the amplitude spectra of some δ Sct stars, for example KIC 11754974 (Murphy et al 2013) and KIC 8054146 (Breger et al 2012;Breger & Montgomery 2014), where the astrophysical implications and uses of the combination frequencies are more uncertain than for white dwarf stars.…”
Section: Introductionmentioning
confidence: 99%
“…Wu 2001 andMontgomery 2005). Combination frequencies dominate the amplitude spectra of some δ Sct stars, for example KIC 11754974 (Murphy et al 2013) and KIC 8054146 (Breger et al 2012;Breger & Montgomery 2014), where the astrophysical implications and uses of the combination frequencies are more uncertain than for white dwarf stars.…”
Section: Introductionmentioning
confidence: 99%
“…The above computation of the frequency spacings also allowed a comparison with the results of Chapellier et al (2012) and Breger et al (2012), where frequency spacings from the dominant δ Scuti frequencies were found to match those of the high-amplitude γ Doradus frequencies. A search for frequency combinations in the spectroscopic data revealed only a possible link between f7, f8 and f35.…”
Section: Characteristic Spacingsmentioning
confidence: 84%
“…The spectroscopic frequency results are surprising and show several unexplained phenomena, yet the clear distinction in the shape of the standard deviation and phase profiles of the higher and lower frequencies that are found suggests an interesting physical origin. With the recent studies of hybrids in the Kepler field as a whole Balona et al 2011;) and individual CoRoT and Kepler (Chapellier et al 2012) and kic 8054146 (Breger et al 2012 hybrid stars (Chapellier et al 2012;Breger et al 2012) more questions are raised about these stars. The existence of the hybrid phenomenon is already in question and the spectroscopic results for HD 49434 so far add weight to both sides of the debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, García Hernández et al (2009Hernández et al ( , 2013 found recurrent frequency spacings in two δ Scutis observed by CoRoT, thereby allowing the construction of an echelle diagram in the latter case. Similarly, Breger et al (2012Breger et al ( , 2013 found multiple sequences of very uniformly spaced frequencies in a δ Scuti observed by Kepler. These observations show that although the pulsation spectra of δ Scuti stars lack the simple frequency patterns present in solar-type pulsators, regular patterns do exist in such stars and need to be explained.…”
Section: Introductionmentioning
confidence: 83%